2001
DOI: 10.1002/jsfa.903
|View full text |Cite
|
Sign up to set email alerts
|

Organic agriculture: does it enhance or reduce the nutritional value of plant foods?

Abstract: The possible differences between organic and conventional plant products are examined from the view of possible effects on human health. It is concluded that nutritionally important differences relating to contents of minerals, vitamins, proteins and carbohydrates are not likely, primarily since none of these are de®cient in typical First World diets, nor are present levels of pesticide residues in conventional products a cause for concern. However, there is reason to believe that contents of many defence-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
233
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(247 citation statements)
references
References 32 publications
9
233
0
5
Order By: Relevance
“…Comprehensive studies have shown clear advantages for several parameters describing a higher product quality of organic produce compared to products derived from mainstream agriculture (Baker et al 2002;Benbrook 2015). The limited availability and uptake of nitrogen is considered as responsible for the often higher contents of secondary metabolites as beneficial ingredients in organic products compared to conventional (Mozafar 1993;Brandt and Molgaard 2001;Köpke 2005). …”
Section: Food Quality and Healthmentioning
confidence: 99%
“…Comprehensive studies have shown clear advantages for several parameters describing a higher product quality of organic produce compared to products derived from mainstream agriculture (Baker et al 2002;Benbrook 2015). The limited availability and uptake of nitrogen is considered as responsible for the often higher contents of secondary metabolites as beneficial ingredients in organic products compared to conventional (Mozafar 1993;Brandt and Molgaard 2001;Köpke 2005). …”
Section: Food Quality and Healthmentioning
confidence: 99%
“…Wzrasta zainteresowanie żywnością ekologiczną, uznawaną za bardziej bezpieczną dla zdrowia człowieka [5,12,25]. Produkcja żywności ekologicznej wyklucza moż-liwość stosowania pestycydów i nawozów mineralnych, a dopuszcza stosowanie nawozów organicznych [20].…”
Section: Wprowadzenieunclassified
“…A limited number of research studies have compared nutritional content in organic and conventionally grown vegetables rather than fruit, with very few examining phytochemical content (reviewed in [35,191]). In general the evidence suggests little difference in the nutritional content of organically cultivated crops with the exception that levels of nitrates are lower and levels of vitamin C and dry matter content may higher than in conventionally grown crops [18,142,181,183]. Some reports suggest increased levels of phytochemicals in organically grown crops [187,191] and some authors have suggested that phytochemicals which can be considered as defence related secondary metabolites could be considerably higher in organic vegetables [18].…”
Section: Means Of Production -Organic and Conventional Agriculturementioning
confidence: 99%